Kenya : the struggle for democracy - Murunga, Godwin R.; Nasong'o, Shadrack Wanjala (Africa in the new millennium., 2007)
This uniquely comprehensive study of Kenya's political trajectory shows how the struggle for democracy has been waged in civil society, through opposition parties, and amongst traditionally marginalised groups like women and the young.